2018
DOI: 10.1111/all.13413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD34+ hematopoietic cells in systemic mastocytosis: Potential role in disease dissemination

Abstract: The presence of the KIT D816V mutation in PB of ISM patients is associated with (early) involvement of circulating CD34 HPC and multiple myeloid cell subpopulations, KIT-mutated PB CD34 HPC potentially contributing to early dissemination of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Previous studies have shown that eosinophils are usually clonal in patients with advanced SM [17][18][19]. However, eosinophilia can also be caused by other pathologic conditions such as parasitosis, drug reactions, or atopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that eosinophils are usually clonal in patients with advanced SM [17][18][19]. However, eosinophilia can also be caused by other pathologic conditions such as parasitosis, drug reactions, or atopia.…”
Section: Discussionmentioning
confidence: 99%
“…Note that for PFS, the Y-axis is cut at 40%. The p value refers to the comparison of the survival curves as assessed by log rank test 230 1711 (21) 15 (19) 3 1028 (14) 705 (30) Organomegaly, number (%) 1 72 721 (8) 21 7108 (8) 35 ( 12 467 54 814 183 (10) 37 (18) 159 (7) Number absolute eosinophils > 1.5 × 10 9 /l (% of that category) 0 0 0 0 10 13 611 (14) 5 (17) 45 (22) 74 (…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…64 Cell culture experiments of CD34 1 CD203c 1 bone marrow progenitors show evidence of mast cell-forming potential and considerable basophil-forming potential; however, the mast cell-forming potential is comparable in the CD34 1 CD203c 2 and CD34 1 CD203c 1 fractions. 64 Still, recent data suggest that CD203c in combination with other markers enrich for mast cell progenitors, 65 likely the more differentiated ones, although this needs to be verified experimentally.…”
Section: Identification Of Early Progenitors With Mast Cell-forming Cmentioning
confidence: 99%
“…56,67 An independent study showed that these progenitors fully agree in phenotype and frequency with the CD34 1 c-Kit hi HLA-DR 2/int CD203c 1 gating strategy used for identifying a putative peripheral blood mast cell progenitor. 65 The Lin 2 CD34 1 c-Kit int/hi FceRI 1 cells constitute unipotent (or almost committed) progenitors, which are further characterized by the expression of CD123 and integrin b7 and absence of CD45RA and CRTH2, placing the cells in the classic CMP sorting gate. 56,67 However, this does not necessarily mean that mast cells are derived from CMPs.…”
Section: Identification Of Early Progenitors With Mast Cell-forming Cmentioning
confidence: 99%
“…11 When the KIT D816V mutation is present in mast cells, it may also be detected in mature bone marrow or peripheral blood cells, such as basophils, eosinophils, neutrophils, and B and T lymphocytes, which depends on the patient. 1217 Furthermore, the precursors of erythroid and myeloid cells as well as CD34 + progenitors may carry the KIT D816V mutation. 12,18,19 Taken together, these findings suggest that the mutation may arise in early hematopoietic stem and progenitor cells (HSPCs), rather than in a lineage-restricted precursor.…”
Section: Introductionmentioning
confidence: 99%